An Evolutionary Study of Carex Subg. Psyllophorae (Cyperaceae) Sheds Light on a Strikingly Disjunct Distribution in the Southern Hemisphere, With Emphasis on Its Patagonian Diversification - Benítez-Benítez, Carmen; Otero, Ana; Ford, Kerry A.; García-Moro, Pablo; Donadío, Sabina; Luceño, Modesto; Martín-Bravo, Santiago; Jiménez-Mejías, Pedro (Frontiers in Plant Science, 2021)
Carex subgenus Psyllophorae is an engaging study group due to its early diversification compared to most Carex lineages, and its remarkable disjunct distribution in four continents corresponding to three independent sections: sect. Psyllophorae in Western Palearctic, sect. Schoenoxiphium in Afrotropical region, and sect. Junciformes in South America and SW Pacific. The latter section is mainly distributed in Patagonia and the Andes, where it is one of the few Carex groups with a significant in-situ diversification. We assess the role of historical geo-climatic events in the evolutionary history of the group, particularly intercontinental colonization events and diversification processes, with emphasis in South America. We performed an integrative study using phylogenetic (four DNA regions), divergence times, diversification rates, biogeographic reconstruction, and bioclimatic niche evolution analyses. The crown age of subg. Psyllophorae (early Miocene) supports this lineage as one of the oldest within Carex. The diversification rate underwent a slowdown through time in the whole subgenus. Geography seems to have played a primary role in the diversification of subg. Psyllophorae. Inferred divergence times imply a diversification scenario away from primary Gondwanan vicariance hypotheses and suggest long-distance dispersal-mediated allopatric diversification. Section Junciformes remained in Northern Patagonia since its divergence until Plio-Pleistocene glaciations. Andean orogeny appears to have acted as a northward corridor, which contrasts with the general pattern of North-to-South migration for temperate-adapted organisms. A striking niche conservatism characterizes the evolution of this section. Colonization of the SW Pacific took place on a single long-distance dispersal event from South America. The little ecological changes involved in the trans-Pacific disjunction implies the pre-adaptation of the group prior to the colonization of the SW Pacific. The high species number of the section results from simple accumulation of morphological changes (disparification), rather than shifts in ecological niche related to increased diversification rates (radiation).